Benevolence and universalism as sustainable entrepreneurship mindset triggers on undergraduate students - Pérez Núñez, Sylvia Mónica; Martínez Flores, Raúl; Woolfolk-Ruiz, Diana E. (My University, 2023)
This study’s purpose is to statistically measure the differences between values perception of first- and fourth-year undergraduate students by evaluating the relative importance of the values of the self-transcendence spectrum, universalism, and benevolence as triggers of the sustainable entrepreneur’s mindset. Educating for sustainability means students’ engagement in projects and initiatives that nurture a sustainable mindset. Values do matter when it comes to sustainability focus business. Using the Schwartz human value scale to address values at the heart of education for sustainability, and a sample of 236 undergraduate students, we found evidence that the value of benevolence moves up the scale on the values profile once the fourth-year students are exposed to projects and initiatives that nurture the development of students’ sustainable mindset. Understanding the values profile of undergraduate students should help practitioners, policy makers, and those on the frontlines of entrepreneurial education identify and develop entrepreneurs’ mindsets in addressing sustainable challenges. RESUMEN El propósito de este estudio es medir estadísticamente las diferencias entre la percepción de valores de los estudiantes de primer y cuarto año de pregrado, evaluando la importancia relativa de los valores del espectro de la autotrascendencia, el universalismo y la benevolencia como desencadenantes de la mentalidad del emprendedor sustentable. Educar para la sostenibilidad significa la participación de los estudiantes en proyectos e iniciativas que fomentan una mentalidad sostenible. Los valores sí importan cuando se trata de negocios enfocados en la sustentabilidad. Usando la escala de valores humanos de Schwartz para abordar valores en el corazón de la educación para la sustentabilidad, y una muestra de 236 estudiantes universitarios, encontramos evidencia de que el valor de la benevolencia sube en la escala en el perfil de valores una vez que los estudiantes de cuarto año están expuestos a proyectos e iniciativas que fomentan el desarrollo de la mentalidad sostenible de los estudiantes. Comprender el perfil de valores de los estudiantes universitarios debería ayudar a los profesionales, a los responsables de la formulación de políticas y a quienes se encuentran en la primera línea de la educación empresarial a identificar y desarrollar la mentalidad de los empresarios para abordar los desafíos sostenibles.
Journal of International councils for Small Business
Keywords: Sustainable mindset; Values; Benevolence; Universalims; Campus Tijuana